POSSIBILITIES OF BIOLOGICAL PROTECTION OF FORESTS AGAINST HARMFUL ORGANISMS (British Journal of Global Ecology and Sustainable Development, 2023)
The main goal of the biological protection of forest trees is to obtain environmentally friendly products while maintaining the biological diversity of biocenoses. The use of biological protection in forests helps to reduce chemical treatments and preserve the number of beneficial organisms in nature. Until now, in the conditions of the Republic of Uzbekistan, the need to use a biological method of combating pests of forest and ornamental trees has not been felt. Based on this, information is provided on the possibility of using a biological method of combating harmful organisms.